2016
DOI: 10.1021/acsnano.6b01142
|View full text |Cite
|
Sign up to set email alerts
|

Nanowire Magnetoscope Reveals a Cellular Torque with Left–Right Bias

Abstract: Cellular force regulates many types of cell mechanics and the associated physiological behaviors. Recent evidence suggested that cell motion with left-right (LR) bias may be the origin of LR asymmetry in tissue architecture. As actomyosin activity was found essential in the process, it predicts a type of cellular force that coordinates the development of LR asymmetry in tissue formation. However, due to the lack of appropriate platform, cellular force with LR bias has not yet been found. Here we report a nanow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 48 publications
2
51
0
Order By: Relevance
“…To visualize the actin filaments, we applied fluorescence staining of actin on different substrates. Circular micropatterns were used for the analysis of the actin cytoskeleton because they provide a geometric confinement of the cell shape that highlights the classification of the transverse arc and dorsal stress fibers of individual cells [ 7 ]. When cells were cultured in circular micropatterns on a rigid substrate, clear actin stress fibers can be observed ( Figure 5 a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To visualize the actin filaments, we applied fluorescence staining of actin on different substrates. Circular micropatterns were used for the analysis of the actin cytoskeleton because they provide a geometric confinement of the cell shape that highlights the classification of the transverse arc and dorsal stress fibers of individual cells [ 7 ]. When cells were cultured in circular micropatterns on a rigid substrate, clear actin stress fibers can be observed ( Figure 5 a).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we further demonstrated that actin stress fibers play a vital role in the formation of a chiral pattern of C2C12 cells. Actin stress fibers can generate a contractile force, which controls the formation of focal adhesion [ 7 , 9 , 15 ]. Meanwhile, actin stress fibers can be regulated by the substrate stiffness, which is also responsible for cell mechanosensing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We next tested whether the hMSC chirality exists in nucleus rotation of single cells. [13,21] Individual cells were seeded onto cell-adherent circular patterns surrounded by pluronic coating ( Figure 1D). With reference to the long-axis of cell nucleus, the transient angular velocity of cell nucleus was recorded at each 10 min interval, and the percentages of transient CW and ACW rotation within the observation duration were compared to determine the rotational bias ( Figure 1D).…”
Section: Chirality Of Hmscsmentioning
confidence: 99%
“…Previous findings revealed that, when cells are cultured on circular islands, their actin cytoskeleton forms a CW-or ACW-biased swirl pattern of dorsal stress fibers that are unidirectionally tilted with a tangential shift of transverse arc. [13,15,21,43] After the rotational assay on gear patterns mentioned above, the cells were fixed and stained ( Figure 1F). Automated image processing was used to analyze the tilting angle of actin filament with respect to the radial axis of each cell.…”
Section: Chirality Of Hmscsmentioning
confidence: 99%